Обґрунтування поняття «державний бюджетний аудит» - Рябчук, Оксана Григорівна; Гожуловський, Сергій Сергійович; Оксана, Рябчук (Гуманітарний університет "ЗІДМУ", 2020)
У статті обґрунтовано необхідність підвищення ефективності сфери, яка фінансується за кошти державного бюджету. Доведено, що таке покращення буде забезпечуватися за умов удосконалення і посилення функції контролю щодо ефективного та доцільного використання державних фінансів. Обґрунтовано, що саме державний фінансовий аудит, який проводиться в межах державного фінансового контролю, потребує детального вивчення, наукового осмислення його сутності та уточнення термінології. У свою чергу, науково обґрунтована та законодавчо визначена термінологія буде основою для розроблення концепції створення системи контролю за державними фінансами, яка відповідає високим світовим стандартам. Розглянуто та проаналізовано існуючі підходи до розуміння змісту державного фінансового та державного бюджетного аудиту. Наведено власне обґрунтоване визначення поняття державного бюджетного аудиту. Наведено основні характеристики видів державного фінансового аудиту в контексті авторського переосмислення його сутності.

Public sector activity provide the most important components of society. The changes that have taken place in the system of public finance control in recent years are fully justified by the policy pursued by Ukraine to move closer to the European Union. State financial audit, conducted within the framework of state financial control, needs detailed studying. Understanding and justifying this category is an extremely important scientific process. Methods that used during the researching: chronology, analysis, synthesis, grouping, generalization, deduction, induction, comparison, analogy, logical reasoning method, dialectics, etc. Public financial audit research addresses a number of theoretical issues related to the need to legislate and differentiate between the concepts of “state financial audit”, “state budget audit”, “tax audit” and “customs audit”. The presence of different definitions of the concepts of "state financial audit" and "state budget audit" is caused by problems of understanding of their essence by scientists and practitioners. However, the main disadvantage of some of the definitions of the budget audit is that they do not mention such an important category as "efficiency". After all, the evaluation of the effectiveness of management decisions and the use of public resources is a feature of the state budget audit. The principle of efficiency is one of the basic principles of the budgetary system, which is defined by the Budget Code of Ukraine. The main purpose of auditing the efficiency of public funds is to determine the cost-effectiveness, efficiency and effectiveness of their use, to establish criteria for evaluating the results obtained and assessing the achievement of the expected goal, drawing conclusions and developing proposals for improving the efficiency of budget spending and eliminating the identified shortcomings. Further research in the areas of state financial audit and state budget audit is very important from a theoretical and practical point of view. Our terminology will allow us to define the composition and structure of the control bodies, their powers, functions, tasks, areas of activity, objects of control, methods of verification, for example, in the development of regulatory and legislative acts.
Keywords: бюджет; аудит; фінанси; державний сектор економіки; контроль; ресурси; категорія; дефініція; budget; audit; finance; public sector economy; control; resources; category; definition